2012
DOI: 10.1179/1743277412y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

“I Never Use ‘Maps’ Anymore”: Engaging with Sat Nav Technologies and the Implications for Cartographic Literacy and Spatial Awareness

Abstract: It is somewhat paradoxical that at a time of widespread and increasing adoption of Satellite Navigation (Sat Nav) technologies of wayfinding, geographic and cartographic research has engaged very little with issues relating to their impact on spatial awareness and cartographic literacy. Through exploration of geography students’ engagements with Sat Nav, we investigate how these latest forms of wayfinding technologies are influencing choice and methods of navigation and how they affect attitudes towards more ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
18
0
4
Order By: Relevance
“…The incentive to actively develop this research was reinforced by the outcomes of the questionnaire survey of new Level 4 students (the same as the one conducted in 2010 and 2011), which revealed that use of smart phones or other Sat Nav-enabled mobile phones for navigation purposes was now virtually ubiquitous at 97% in comparison to 71.4% in 2011 and 54% in 2010 as reported by Speake and Axon (2012). We thought it timely to find out more about how, and where, young people were using Sat Nav technology to wayfind.…”
Section: Growing a Learning Community: Contexts And Structuresmentioning
confidence: 98%
“…The incentive to actively develop this research was reinforced by the outcomes of the questionnaire survey of new Level 4 students (the same as the one conducted in 2010 and 2011), which revealed that use of smart phones or other Sat Nav-enabled mobile phones for navigation purposes was now virtually ubiquitous at 97% in comparison to 71.4% in 2011 and 54% in 2010 as reported by Speake and Axon (2012). We thought it timely to find out more about how, and where, young people were using Sat Nav technology to wayfind.…”
Section: Growing a Learning Community: Contexts And Structuresmentioning
confidence: 98%
“…This may be in response to user preferences. Users' turn from paper to digital maps is noticeable, especially when it comes to the navigational functions (Axon et al 2012;Speake & Axon 2013;Speake 2016). The disproportion may also be connected with the use of map applications prepared for the study and/or use of eye-tracking, which is often used as a supplementary method ).…”
Section: Map Mediummentioning
confidence: 99%
“…While familiarity with space can produce the spatial knowledge used to generate cognitive maps, research has shown that GPS and automatic navigation systems do not improve spatial awareness (Huang et al, 2012;Speake and Axon, 2012), and that these systems can create 'passive operators' with a degraded ability to acquire spatial knowledge (Parush et al, 2007). If AR is to be applied to emergency management with the purpose of improving spatial awareness, it must enhance the user's ability to comprehend the topology of complex multilevel spaces by providing allocentric representations of space instead of egocentric guidance through space.…”
Section: Mixed Realitymentioning
confidence: 99%